2020
DOI: 10.1155/2020/5257896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Prognostic Biomarkers for Breast Cancer Based on lncRNA-TF-Associated ceRNA Network and Functional Module

Abstract: Breast cancer leads to most of cancer deaths among women worldwide. Systematically analyzing the competing endogenous RNA (ceRNA) network and their functional modules may provide valuable insight into the pathogenesis of breast cancer. In this study, we constructed a lncRNA-TF-associated ceRNA network via combining all the significant lncRNA-TF ceRNA pairs and TF-TF PPI pairs. We computed important topological features of the network, such as degree and average path length. Hub nodes in the lncRNA-TF-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…A transcription factor (TF) called ZNF410, also referred to as APA-1, regulates the expression of genes involved in matrix remodeling during the senescence of fibroblasts [43]. The research on ZNF410 is lacking, yet, the latest cancer research reported the association of abnormal expression of this gene in breast cancer with tumor stage and different subtypes [44]. CBWD5, also known as CBWD3, is currently only reported to have copy number variation in CBWD5 in small cell lung cancer [45].…”
Section: Rasg Associated With Rbps In Tumorsmentioning
confidence: 99%
“…A transcription factor (TF) called ZNF410, also referred to as APA-1, regulates the expression of genes involved in matrix remodeling during the senescence of fibroblasts [43]. The research on ZNF410 is lacking, yet, the latest cancer research reported the association of abnormal expression of this gene in breast cancer with tumor stage and different subtypes [44]. CBWD5, also known as CBWD3, is currently only reported to have copy number variation in CBWD5 in small cell lung cancer [45].…”
Section: Rasg Associated With Rbps In Tumorsmentioning
confidence: 99%